Dos invasion at network by intruder; protection mecha-nism by â€œanti-dos invasion firewallâ€ - S., Govindaraj; S., V. Khanaa; Rukkumani, C. (International Journal of Engineering and Technology, 2017)
Every cyber-warfare done by criminal perpetrators motto is not to know information and data, but are interested in denial of service assaults which never attempt to breach the security or firewall, Rather to intend the network surge for particular span of time and denial of access which ultimately target end legitimate user through two method of DOS attack (crash service or flooding service).The main problem with the â€œDenial Of Serviceâ€ attack that it will lead to network surge or corruption of data which is transfer or processed from source to destination via some transmission techniques through network.